1993
DOI: 10.1111/j.1469-8137.1993.tb03822.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition between diploid and derivative autotetraploid Dactylis glomerata L. from Galicia. Implications for the establishment of novel polyploid populations

Abstract: SUMMARYThe competitive ability of a tetraploid, and its morphologically indistinguishable progenitor diploid Dactylis glomerata L., from Galicia (Spain), was tested in a two-year study, using isolated plants and the same individuals grown at two densities (16 and 36 plants per pot, respectively). Inverse linear regression equations were used to quantify the response of the different ploidy levels (hereafter cytotypes) to density. For the diploids, inter-cytotype competition coefficients were significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
3
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 40 publications
7
87
3
1
Order By: Relevance
“…However, studies of competition between diploid and tetraploid populations have provided evidence that bears indirectly on minority cytotype processes. For example, Maceira et al (1993) found that diploid and tetraploid Dactylis grown in association had reduced seed production compared with pure stands and that both cytotypes were a¡ected equally. In addition, studies of phenotypic selection on £owering time in sympatric populations of diploid and tetraploid Anthoxanthum alpinum indicated that ¢tness varies as a function of the degree of £owering overlap (Bretagnolle 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of competition between diploid and tetraploid populations have provided evidence that bears indirectly on minority cytotype processes. For example, Maceira et al (1993) found that diploid and tetraploid Dactylis grown in association had reduced seed production compared with pure stands and that both cytotypes were a¡ected equally. In addition, studies of phenotypic selection on £owering time in sympatric populations of diploid and tetraploid Anthoxanthum alpinum indicated that ¢tness varies as a function of the degree of £owering overlap (Bretagnolle 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, polyploidy can influence genetic variation (e.g., Klekowski and Baker 1966;Roose and Gottlieb 1976;Soltis and Rieseberg 1986;Moody et al 1993;Ainouche et al 1995;Purdy and Bayer 1995;Song et al 1995;Ehrendorfer et al 1996), life histories (e.g., Marks 1966;Smith and Phipps 1988;Barrett 1989;Husband and Schemske 1997), morphology (e.g., Khare and Kaur 1983;Patwary et al 1989;Chmielewski 1994;Vandenhout et al 1995), physiology (e.g., Tiwari et al 1980;Levin 1983;Koul et al 1985;Bhargava et al 1988; Warner and Edwards 1989;Griesbach and Kamo 1996;Letchamo 1996), and geographic distributions (e.g., Tothill and Hacker 1976;Novak et al 1991; Van Dijk 2 Present address: Department of Biology, Vanderbilt University, Box l8l2-B, Nashville, Tennessee 37235; E-mail: k.segraves@ vanderbilt.edu. Lamade et al 1994; Husband and Schemske 1998).In angiosperms, two other common effects of polyploidy are shifts in the timing of flowering (Tothill and Hacker 1976;Garbutt and Bazzaz 1983;Lumaret et al 1987;Lumaret 1988;Lumaret and Barrientos 1990; Van Dijk et al 1992;Maceira et al 1993;Bretagnolle and Lumaret 1995;Petit et al 1997) and changes in floral morphology (Giles 1942;Smith 1946;Kliphuis 1972;Taylor...…”
mentioning
confidence: 99%
“…On the other hand, ploidy-altered traits may translate to better polyploid performance in competition either with its diploid progenitor or with other species. Studies experimentally addressing competition between diploids and their naturally-occurring, recently arisen autopolyploid derivatives are, however, very rare and either support this view (Maceira et al, 1993) or show no difference (Thompson et al, 2015). Alternatively, ploidy-altered traits may also help to cope with competition with other species and may broaden niches, opening the possibility to escape from minority cytotype exclusion.…”
Section: Cytotype and Competitive Exclusionmentioning
confidence: 99%
“…Assuming that interploidy matings are more likely to produce inviable or sterile offspring, rare cytotypes should have reduced relative fitness. Such a frequency-dependent mating disadvantage was described from experimental and natural mixed-ploidy populations (Hagberg and Elleström, 1959;Maceira et al, 1993;Husband, 2000;Baack and Stanton, 2005;Mráz et al, 2012), but only a few studies further evaluated its significance for polyploid establishment. Interestingly, studies of mixed-ploidy populations of Chamerion angustifolium indicate a surprising asymmetry in this relationship between ploidies.…”
Section: Cytotype and Competitive Exclusionmentioning
confidence: 99%